Analysis of Clay Silt Reserve Using Geoelectricity in the Village of Dulohupa District of Gorontalo - Dewa Gede Eka Setiawan; Abd. Wahidin Nuayi (Journal of Applied Geospatial Information, 2017)
This research aims to investigate clay silt reserve in brick farmer area. This research applies geoelectricity by using Schlumberger configuration conducted by doing injection of electric current with low frequency to surface of earth. Value of resistance will bring information about structure and materials across by it.Research site is in four stations and based on the geographical location in the station I at coordinate N 00 ° 35'43.7 ", E 123 ° 03'41.6" directed to east west, station 2 in coordinate N 00 ° 35'43.8 ", E 123 o 03'41.4 "directed to north south, station 3 in coordinate N 00 ° 35'42.4", E 123 ° 03'41.5 "directed to north south and station 4 in coordinate N 00 ° 35'45.4", E 123 ° 03 '42 .1 "directed to south north. Research finding reveals that depth or density of clay silt ie in S1 is 8 m, in S2 is 2.5 m, in S3 is 7 m while in S4 is 8,5 m. Density in S2 is the thinnest is the river thinnest gravel and sand are found there. Then, based on the four points after straight line is drawn, it shapes geometry which makes the volume of clay silt reserve can be calculated. And based on finding of measurement and calculation, it obtains volume of clay silt reserve in the village of Dulohupa for 15000 m3.